2009
DOI: 10.1143/jjap.48.026503
|View full text |Cite
|
Sign up to set email alerts
|

Photoresist Removal Using Atomic Hydrogen Generated by Hot-Wire Catalyzer and Effects on Si-Wafer Surface

Abstract: We investigated an environmentally friendly method using atomic hydrogen generated by contact catalysis on a tungsten hot-wire catalyzer to remove photoresist instead of using chemicals and its effects on a Si-wafer surface. We eventually obtained a photoresist removal rate of 2.5 mm/min attributable to a reaction of atomic hydrogen with a positive-tone novolak photoresist, without thermal shrinkage of the photoresist film during atomic hydrogen irradiation because the photoresist shrank only under the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…Some findings related to the use of atomic hydrogen generated on a tungsten hot-wire catalyst for photoresist removal have already been reported [10][11][12][13][14][15][16]. In a past study we achieved a best removal rate of 2.5 μm/min using atomic hydrogen by heating up the catalyst and the substrate [12].…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Some findings related to the use of atomic hydrogen generated on a tungsten hot-wire catalyst for photoresist removal have already been reported [10][11][12][13][14][15][16]. In a past study we achieved a best removal rate of 2.5 μm/min using atomic hydrogen by heating up the catalyst and the substrate [12].…”
Section: Introductionmentioning
confidence: 70%
“…It should be noted that the H-atom density saturates against the H 2 pressure under such high pressure conditions [26] and that the H atoms produced may be completely thermalized before arriving at the substrate surfaces. In our past study, we reported that the removal rate increases with hydrogen pressure between 0.4 and 7.2 Pa [12]. This increase can easily be ascribed to the increase in the H-atom density [26].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations